Modelling for sustainable development: New decisions for a new age - Bassi, Andrea; Casier, Liesbeth; Laborde Debucquet, David; Linsen, Max; Manley, David; Maennling, Nicolas; Mann, Howard; Siersted, Morten; Smaller, Carin; Steel, Iain; Uzsoki, David; West, Johnny (International Institute for Sustainable Development, 2019)
Our environmental, economic, and social systems are currently facing a host of challenges, which if left unaddressed will have significant implications for the world in which we live. Tackling these challenges will require better-informed decision-making, which in turn requires models that are designed and developed with sustainable development considerations and objectives in mind. To support this need for better-informed decision making, this book brings together the insights and expertise of a dozen expert modellers and policy analysts, who completed this project on modelling for sustainable development in June 2019 using the "Book Sprints" method. It outlines the different modelling approaches available; describes why model design and development matters for sustainable development; and explains how these models can contribute to decision-making processes. The book is designed for decision-makers, model commissioners, model developers, model users, and students specializing in modelling and/or the different aspects of sustainable development.